2014
DOI: 10.1063/1.4902162
|View full text |Cite
|
Sign up to set email alerts
|

Broadband diodelike asymmetric transmission of linearly polarized light in ultrathin hybrid metamaterial

Abstract: Articles you may be interested inA linear-to-circular polarization converter with half transmission and half reflection using a single-layered metamaterial Appl. Phys. Lett. 105, 021110 (2014); 10.1063/1.4890623 Unidirectional transmission using array of zero-refractive-index metamaterials Appl. Phys. Lett. 104, 193509 (2014); 10.1063/1.4878400 Broadband asymmetric transmission of optical waves from spiral plasmonic metamaterials Appl. Phys. Lett. An experimental verification of metamaterial coupled enhanced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 25 publications
0
48
0
Order By: Relevance
“…Further developments showed that bi-layer metasurface structures can be used to demonstrate increased bandwidth of the asymmetric transmission in the near infrared [107,108]. It was shown that the interlayer alignment could have very little effect on the asymmetric transmission [107], which also indicates that the near-field coupling is negligible. This advantageous property is particularly useful in the optical regime where the interlayer alignment is challenging.…”
Section: Asymmetric Transmissionmentioning
confidence: 99%
“…Further developments showed that bi-layer metasurface structures can be used to demonstrate increased bandwidth of the asymmetric transmission in the near infrared [107,108]. It was shown that the interlayer alignment could have very little effect on the asymmetric transmission [107], which also indicates that the near-field coupling is negligible. This advantageous property is particularly useful in the optical regime where the interlayer alignment is challenging.…”
Section: Asymmetric Transmissionmentioning
confidence: 99%
“…The hybrid metasurface consists of an L-shaped metallic layer and a nanorod layer. With x-polarized incidence, the forward and backward transmission reveals a great diference between 1200 and 1500 nm [47], the simulated results of which are illustrated in Figure 6f. It should be noticed that asymmetric transmission is diferent from optical isolator, which can only be atained with nonreciprocal-active devices.…”
Section: Asymmetric Transmissionmentioning
confidence: 93%
“…In our simulations, the dielectric function of gold is defined by Drude mode with plasmon frequency ω p = 1.37 × 10 16 s −1 and damping constant Îł = 4.08 × 10 13 s −1 [22]. To account for surface scattering, grain boundary effects in the thin gold film and inhomogeneous broadening, we used a three times higher damping constant than bulk [23,24]. We firstly do not con- sider the presence of the dielectric spacer and substrate in our design (the permittivity of the dielectric is 1), which may be required in its practical realization.…”
Section: Design and Characteristicsmentioning
confidence: 99%
“…Considering the shift of the inclusion resonance caused by the dielectric spacer and substrate, a high performance polarization conversion with a 1000 nm bandwidth at the range of 1000-2000 nm can still be realized by optimizing the parameters of the ultrathin hybrid metamaterial with: P = 500 nm, L 1 = 290 nm, W 1 = 100 nm, L 2 = 300 nm , L 3 = 370 nm, W 2 = 50 nm, W 3 = 50 nm, s = 50 nm, t 1 = 30 nm, and t 2 = 250 nm. Moreover, the practical fabrication of such ultrathin hybrid metamaterial can be realized by using electron-beam lithography, evaporation deposition of gold, and plasma-enhanced chemical vapor deposition of silicon dioxide [24].…”
Section: Design and Characteristicsmentioning
confidence: 99%